Six Sigma implementation barriers in Indian industries – survey results and case studies. (4th January 2010) - Desai, Darshak A.; Patel, M.B.
From the researches and surveys conducted and published so far, it appears that Six Sigma is not being explored by the Indian industries to its full potential. This paper highlights a research study conducted to ascertain the implementation hurdles Indian industries are facing in Six Sigma implementation and thus failing to gain appropriate benefits from the same. It also presents two real life case studies highlighting Six Sigma implementation difficulties in Indian industries. The cases are the industries where Six Sigma was not tried before. Six Sigma was applied on to their chronic problems keeping in view the findings of the analysis of Six Sigma implementation barriers in Indian industries. The implementation trial was successful, encouraging the Indian industries to overcome the typical implement barriers of Six Sigma quality improvement drive and go for the same with full swing for overall operational excellence.